Macromol. Rapid Commun. 23/2014. Issue 23 (December 2014) - Bianchi, Alberto; Mauri, Michele; Bonetti, Simone; Koynov, Kaloian; Kappl, Michael; Lieberwirth, Ingo; Butt, Hans‐Jürgen; Simonutti, Roberto
<x xml:space="preserve">Abstract</x> Back Cover: Poly(N, N‐dimethylacrylamide)‐block‐polystyrene copolymers with a very short hydrophilic block (PDMA10‐b‐PS62) self‐assemble in large nanoparticles with hierarchical structure. Primary micelles with a diameter of about 15 nm and thin PDMA coronas stick together with coronas of other micelles generating larger objects. The possibility to disassemble these hierarchical nanoparticles, either by a mechanical or chemical stimulus, can be exploited for developing new drug carriers. Further details can be found in the article by A. Bianchi, M. Mauri, S. Bonetti, K. Koynov, M. Kappl, I. Lieberwirth, H.‐J. Butt, and R. Simonutti* on page 1994. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>